1989
DOI: 10.1002/bip.360280803
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of size and form in the assembly of collagen fibrils in vivo

Abstract: A possible mechanism for regulating the lateral growth of collagen fibrils in vivo is considered. A growth inhibitor associated with a particular part of the long semiflexible collagen molecule restricts that part of the molecule to the surface of the growing assembly. Lateral accretion ceases when these inhibitors form a complete circumferential layer around the fibril surface. Cell-mediated removal of the inhibitors allows lateral growth to proceed to a second limiting layer, and so on to subsequent limiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 82 publications
2
30
0
Order By: Relevance
“…This is in agreement with in vivo studies, where intermediates are identified as being 8 nm in diameter when dehydrated (9) or 11 nm when hydrated (10), assuming continued assembly from two 4-nm microfibrils.…”
supporting
confidence: 91%
“…This is in agreement with in vivo studies, where intermediates are identified as being 8 nm in diameter when dehydrated (9) or 11 nm when hydrated (10), assuming continued assembly from two 4-nm microfibrils.…”
supporting
confidence: 91%
“…The mean intermolecular spacing in collagen fibrils of uncompressed human cartilage can be estimated as 1.865 nm from measurements of the equatorial x-ray scattering (16). If the number of triple-helical domains in a transverse section through the fibril ϭ N, then the diameter (D eff nm) of the fibril is then given by: D eff ϭ 1.96͌N nm (28).…”
Section: Calculation Of Effective Hydrated Diameter For Model Fibrilmentioning
confidence: 99%
“…1). The N-propeptide has been proposed to inhibit collagen synthesis (17,18) and regulate the diameter of collagen fibrils by inhibiting the lateral growth during fibrillogenesis (19). The N-propeptide of type II procollagen has recently been shown to bind TGF-␤1 and bone morphogenetic protein-2 (BMP-2) and has been proposed to play a role in the extracellular matrix deposition of BMPs in chondrogenic tissue (20).…”
Section: Thrombospondin 1 (Tsp1)mentioning
confidence: 99%